The role of modern construction methods in environmental sustainability at the project site - Alharbi, Ibtisam Marshod (Journal of natural sciences, life and applied sciences, 2023)
This study is concerned with the environmental dimension in the field of sustainable development, and aims to identify the role of modern construction methods used in housing projects in the city of Jeddah in achieving environmental sustainability through the construction materials and waste management index during the construction stage. The study used the descriptive analytical method, and relied on collecting its data on a questionnaire, which was distributed to 32 engineers working on two residential program projects, which were built using some modern construction methods in the city of Jeddah. Through the analytical results of the study data, it can be concluded that modern construction methods contributed to a high degree in achieving the standards of the Sustainable Guide for Residential Buildings 2019 for the on-site materials and construction waste management index. The study proved that modern construction methods contribute primarily, with a relative weight estimated at 90%, to reducing construction waste, whether in the factory or at the construction site. This is to standardize the materials involved in construction operations and reduce the error rate in building and construction work that relies on machines and mechanization within factories.